Sharing luxury possessions in the age of digital experience economy: Consumption type and psychological entitlement - Joya A. Kemper; Xue, Bai; Fang, Zhao; Tung, Moi Chiew; Felix Septianto; Yuri Seo (Elsevier Inc., 2022)
With the advent of the digital experience economy, contemporary luxury brands have embraced social media as an important channel for improving brand perceptions and developing customer relationships. This is because encouraging consumers to share luxury purchases on social media offers a strategic value for luxury brands. The present research investigates the conditions under which consumers are more likely to share luxury (vs. nonluxury) purchases on social media. Across two experiments, we establish that luxury (vs. non-luxury) purchases are shared more when they are associated with material (vs. experiential) consumption, and among consumers with a high (vs. low) sense of entitlement. These findings make several theoretical and managerial contributions, providing avenues for future research on what consumers do with luxury brands on social media.